PHYSICAL ACTIVITY AND DISABILITIES: A POSSIBLE RELATIONSHIP? (Fiep Bulletin - online, 2013)
The regular practice of physical exercises is considered an effective form of fomenting healthy habits that contribute to the life quality, once it provides the people bearers of deficiencies benefits physical, psychological and social, turning possible not only the recognition of your potentialities, as well as, your integration in the society (DUARTE, 2003; LIMA, 2003). The research of descriptive nature with qualitative approach aimed at to analyze the contributions of the physical activity adapted in the quality of the people's bearers of physical deficiency life, tends in view a better social insert. The selected sample in way not intentional probabilistic, was composed by eight athletes of the masculine and feminine goods, being five athletes are of the swimming, two athletes belong to the weightlifting and one athlete of the athletics, in the age group from 21 to 42 years, adopted in SADEF - RN and who participated in the Paralympics Games of Peking 2008. As measure instrument was used a semi-structured interview, identifying the history of the participants' life before and after the practice of the physical activity as well as the motive contributions, partners and psychological of that practice. The results demonstrate that the adapted physical activity being an area that works directly with the body in movement, has the responsibility of offering possibilities and opportunities for all the bodies to be them in the ambit motor, social or psychological, independent of your condition, being characterized as well as a focus inclusion promoter, promotion to the health and life's quality for all the people, mainly the deficiency bearers.
Keywords: Life's Quality; Physical Exercise; Deficiency